Solving Nonlinear Inventory Model for Deteriorating Items using Fractional Differential Method - Jeyanthi, M.V.; Sheik Uduman, P.S. (Journal of Environmental Accounting and Management, 2026)
In this paper, a nonlinear inventory model with demand as a derivative of time is developed for deteriorating items with no shortages are allowed. The model is solved initially by using Differential Transform Method (DTM) and further, the model is modified to Caputo Derivative Fractional Order (CDFO) and solved by Homotopy Perturbation Method with triangular fuzzy initial conditions. The results for both models in terms of non-linearity of DTM and HPM are analyzed and compared numerically.